Let's start from the left side, and manipulate it to get the right side, which would prove the identity.
We know that:
i) [tex]\displaystyle{ \cos(x-y)=\cos x \cos y+\sin x \sin y [/tex]
ii) [tex]\displaystyle{ \cos(x+y)=\cos x \cos y-\sin x \sin y [/tex].
From the above fundamental identities, we can rewrite the left hand side as:
[tex]\displaystyle{ \cos x \cos y+\sin x \sin y-(\cos x \cos y-\sin x \sin y)=[/tex]
[tex]\displaystyle{ \cos x \cos y+\sin x \sin y-\cos x \cos y+\sin x \sin y=2\sin x \sin y[/tex],
which is what we needed to show.